2001
DOI: 10.1159/000049082
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Plasma α1,3-Fucosyltransferase Deficiency and Development of the Methods for Its Genotyping

Abstract: Four patients with mental illness were found to be deficient in plasma α1,3-fucosyltransferase for the first time in Japan [Exp Clin Immunogenet 1999;16:125–130]. Complete sequencing of FUT6 genes in these individuals revealed the presence of two point mutations, i.e., G739 to A (Glu→247 to Lys) and C945 to A (Tyr→315 to stop). In addition to two reported alleles having G739 to A (pf1) and G739 to A and C945 to A (pf3), a new mutated allele having C945 to A (pf2) was found to be present and all the individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…The patient was, therefore, suggested to possess the lethal mutation of the FUT6 gene and to lack serum α1,3fucosyltransferase activity [ 38 ]. In fact, the patient was determined to possess the pf gene homozygously ( pf / pf ) indicating occurrence of lethal mutation in the FUT6 gens which resulted in the absence of fucosylated glycans in AGP [ 37 ]. However, a couple of fucosylated glycans were still detected as less than several % of the total glycans in AGP ( Fig 4b ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The patient was, therefore, suggested to possess the lethal mutation of the FUT6 gene and to lack serum α1,3fucosyltransferase activity [ 38 ]. In fact, the patient was determined to possess the pf gene homozygously ( pf / pf ) indicating occurrence of lethal mutation in the FUT6 gens which resulted in the absence of fucosylated glycans in AGP [ 37 ]. However, a couple of fucosylated glycans were still detected as less than several % of the total glycans in AGP ( Fig 4b ).…”
Section: Resultsmentioning
confidence: 99%
“…Whereas, since all these glycans are synthesized enzymatically through catalytic actions of a series of glycosyltransferases, such enzymes could be an important target to detect glycan-based changes in malignancies involving possible establishment of a novel biomarker for diagnosis of cancer. In fact, our previous studies demonstrated the usefulness of analyzing α1,2- [ 47 49 ], α1,3- [ 20 , 21 , 37 , 38 , 50 54 ], α1,4- [ 55 58 ] and α1,6fucosyltransferase [ 59 ] activities using specific sugar-acceptors, which emphasized the specific role of the fucosylated antigens appeared to play on carcinogenesis [ 1 , 47 49 ]. In particular, significantly elevated activities of α1,3fucosyltransferase in plasma and/or serum have been observed in patients with diverse cancers [ 20 , 21 , 51 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disruption of sphingolipid metabolism could result in widespread effects, related to diverse pathological deficits already described in schizophrenia, including myelination and oligodendrocyte function (Narayan et al 2009). Three fucosyltransferase genes (FUT3, FUT5 and FUT6) map in the duplicated region (Costache et al 1997), and plasma α1,3-fucosyltransferase deficiency was detected in Japanese patients with schizophrenia (Yazawa et al 1999;Tanaka et al 2001). Post-translational protein modifications can have a role in the pathophysiology of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…FUT VI is believed to contribute to sLeX synthesis in the liver or hepatocellular carcinoma HepG2 cells and to be involved in cancer metastasis [15][16][17]. Moreover, the level of α1,3-FUT activity in plasma is elevated in various cancerous conditions [18-α1,3-FUT activity and α1-3-fucosylation of serum glycoproteins [21].…”
Section: Introductionmentioning
confidence: 99%